Corporate Sustainability Performance (CSP), Leverage Adjustment, and Financial Performance - Mukti, Meliani; Kusuma, Indra Wijaya (Jurnal ASET (Akuntansi Riset), 2024)
The study aims to examine the impact of corporate sustainability performance (CSP) on corporate financial performance (CFP) and corporate leverage adjustment of publicly listed companies in Southeast Asia. We studied the indirect effect of CSP on CFP through leverage adjustment using the generalized method of moments to estimate the target of the firm’s leverage. We analyzed 968 firm-year observations from 121 companies from 2012–2019 using generalized least squares. We find that CSP exerts both a direct and an indirect influence on corporate financial performance (CFP). CSP affects CFP positively through leverage adjustment in an indirect manner. CSP encourages the firm to move faster to their target leverage, while the faster leverage adjustment improves corporate financial performance. The indirect effects of CSP on CFP might indicate the substantial financial resources required to undertake CSP initiatives. The results support the stakeholder theory and capital structure theory, with a particular emphasis on the dynamic trade-off theory. Empirical research has indicated that the relationship between CSP and CFP yields varying outcomes, which may imply the existence of confounding variables that we conjecture are associated with corporate capital structure.